Foreign policy models and strategic options: The case of Latin America compared with the United States - Roberto Russell; Juan G. Tokatlian (Revista CIDOB d'Afers Internacionals, 2009)
The essay aims to identify the foreign policy models that have predominated in Latin America in recent years, placing particular emphasis on the decade of the 1990s. Based on a series of premises, trends and conditions, the author examines the region’s strategic options as compared to the United States. The text highlights three alternatives available to Latin American countries, and which could shape links with Washington in the future. These take the form of a series of specific issues and problems that interconnect the United States with Latin America.